Peran Instagram Marketing dan Brand Performance dalam Meningkatkan Brand Loyalty Indomie - Wibowo, Afini Rifa; Yuliati, Nuriah; Nurhadi, Eko (International Journal of Multidisciplinary Research and Literature, 2024)
As one of the pioneers of instant noodles, Indomie also took the lead in promoting its products through Instagram as one of the strategies to communicate and interact with its consumers. However, Indomie's engagement rate on Instagram is below average. It shows that Indomie needs to optimally utilize its Instagram media to drive its followers to connect to prevent the achievement of the objectives of using Instagram as a brand strategy to retain and acquire consumers. This study aims to determine the influence of Instagram marketing and brand performance on Indomie brand loyalty. Data was collected by distributing questionnaires, which will be analyzed using the SEM PLS method. The research results on 81 Indomie consumers who also follow Indomie on Instagram show that Instagram marketing positively and significantly affects brand loyalty. Likewise,  performance shows a positive and significant relationship with brand loyalty. The results of this analysis indicate that Indomie's strategy of using Instagram has the opportunity to reach and listen to consumers more closely. Indomie also has good brand performance in consumers' minds